2000
DOI: 10.1111/j.1349-7006.2000.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Dihydropyrimidine Dehydrogenase and Pyrimidine Nucleoside Phosphorylase Activities by Growth Factors and Subsequent Effects on 5‐Fluorouracil Sensitivity in Tumor Cells

Abstract: Dihydropyrimidine dehydrogenase (DPD) and pyrimidine nucleoside phosphorylase (PyNPase) are the first and rate-limiting enzymes that regulate 5-fluorouracil (5-FU) metabolism, and tumoral DPD activity appears to be a promising predictor of 5-FU sensitivity. However, the regulatory mechanisms determining these enzyme activities have not been fully understood. We investigated the biological effects of epidermal growth factor (EGF) and transforming growth factor (TGF)-α α α α Key words: Dihydropyrimidine dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, since the effect of 5FU is also influenced by the dihydropyrimidine dehydrogenase (DPD) activity, as well as epidermal growth factor and TGF-alpha, the enzymatic activities of TP, DPD and other environmental tumor factors should be studied concurrently. 16 Tokumo et al reported that the TP expression was higher in squamous cell carcinoma than in adenocarcinoma or adenosquamous cell carcinoma of the cervix. 14 However, in our present study, no significant difference in the TP enzymatic activity was found between squamous cell carcinoma and adenocarcinoma/adenosquamous cell carcinoma, although the TP activity had a tendency to be a little higher in the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the effect of 5FU is also influenced by the dihydropyrimidine dehydrogenase (DPD) activity, as well as epidermal growth factor and TGF-alpha, the enzymatic activities of TP, DPD and other environmental tumor factors should be studied concurrently. 16 Tokumo et al reported that the TP expression was higher in squamous cell carcinoma than in adenocarcinoma or adenosquamous cell carcinoma of the cervix. 14 However, in our present study, no significant difference in the TP enzymatic activity was found between squamous cell carcinoma and adenocarcinoma/adenosquamous cell carcinoma, although the TP activity had a tendency to be a little higher in the former.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, from a viewpoint of 5FU activation, which, other than as an angiogenic factor, is one of primary roles of TP, the enzymatic activity of TP in the whole cancer tissues can become an index to estimate the effect of 5FU‐based chemotherapy. However, since the effect of 5FU is also influenced by the dihydropyrimidine dehydrogenase (DPD) activity, as well as epidermal growth factor and TGF‐alpha, the enzymatic activities of TP, DPD and other environmental tumor factors should be studied concurrently 16 …”
Section: Discussionmentioning
confidence: 99%
“…Various reports have clearly shown that DPD activity closely correlates with mRNA levels, indicating that the DPD phenotype is controlled by some transcriptional or post‐transcriptional mechanisms in both normal and cancer cells (18, 40, 41). It has been shown that several factors, including circadian rhythm (15, 28), gender (35), treatment with 5‐FU (42), tegafur (43), epidermal growth factor and transforming growth factor‐α (44, 45), methylation of the DPYD promoter region (46), activator protein‐1 (47), may alter DPYD expression. In this study, we ruled out the possibilities of impact on DPD activity with regard to circadian rhythm and treatment factors.…”
Section: Discussionmentioning
confidence: 99%
“…8) We also reported that these growth factors suppress tumoral DPD activity, increase pyrimidine nucleoside phosphorylase activity, and make tumor cells more sensitive to 5-FU. 9) In the present study, we investigated the biological effects of 5-FU on tumoral DPD activity in the presence or absence of EGF and studied the regulation of DPD activity by 5-FU and EGF.…”
mentioning
confidence: 99%